Environmental and agronomic factors affecting mealybug populations in papaya - Fredrick, Albert; Rahim, Abdul; Adiwena, Muh (Wallacea Plant Protection Journal, 2025)
Mealybug infestations are a growing concern in tropical horticulture due to their rapid population increase and the significant damage they cause to fruit crops. This research examined the severity of attack and population density of mealybugs (Pseudococcidae) on papaya (Carica papaya L.), and analysed their relationship with environmental conditions and cultivation practices in several locations in Tarakan City, North Borneo. The study was conducted from January to April 2025 at seven papaya cultivation sites, including Juata Laut 1–5, Juata Permai, and Karang Harapan. A field survey combined with purposive sampling was applied to assess a minimum of 100 papaya trees over one year old at each site. Data collected included the number of infested trees, mealybug population per plant, types of fertilizers and pesticides used, plant age, and surrounding land conditions. The percentage of trees infested with mealybugs ranged from 25.07% to 38.89%, while the average mealybug population on infested trees ranged from 199.52 to 224.59 individuals per plant. Sites characterized by intensive application of chemical fertilizers and pesticides—such as Juata Laut 2 and Juata Laut 4—showed higher infestation levels than those managed with organic practices, such as Juata Permai. Environmental factors, particularly high humidity and inadequate drainage, were also associated with increased mealybug population growth. These findings indicate that environmental conditions and cultivation techniques play a substantial role in shaping the population dynamics of mealybugs. The results highlight the importance of implementing Integrated Pest Management (IPM) strategies that emphasise ecological approaches and environmentally sustainable cultivation practices to mitigate mealybug infestations in humid tropical regions such as Tarakan City.